(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the partial and simultaneous influence of Work Ethic, Organizational Culture and Work Environment on Organizational Commitment at Villa Danoya Seminyak in Badung. The location of this study was conducted at Villa Danoya Seminyak in Badung with a sample of 35 respondents taken from all employees, using a saturated sample method. Data collection method by observation, interview and questionnaire dissemination. The data analysis techniques used are multiple linear regression analysis, determination coefficient analysis, t test and F test. The results in this study found that partially work ethic, organizational culture and work environment have a positive and significant effect on organizational commitment. The results of simultaneous tests found that work ethic, organizational culture and work environment together have a positive and significant effect on organizational commitment. Suggestions are expected to improve supervision or evaluation of employee work, maintain a conducive work environment and hold regular meetings every month to maintain good employee work commitments